Zygomatic implant-supported prosthetic rehabilitation of a patient with Brown et al. Class II c maxillary defect: A clinical report - Nitasha Gandhi; Sumir Gandhi; Harit Talwar; Kusha Dhawan (Wolters Kluwer Medknow Publications, 2022)
The genesis of acquired maxillary defects poses a significant challenge when it comes to rehabilitating a patient prosthetically. These defects lead to functional and esthetic impairment, affecting the quality of life of an individual. This clinical report describes a satisfactory zygomatic implant-supported overdenture rehabilitation of a patient who underwent subtotal bilateral maxillectomy after an industrial accident. The result shows zygomatic implant-supported overdenture as a viable, predictable, and economical treatment option for a patient with an extensive maxillary defect.